ECTOMYCORRHIZAL FUNGI INCREASED EARLY GROWTH of Shorea balangeran (Korth.) BURCK UNDER NURSERY AND FIELD CONDITIONS IN DEGRADED PEAT SWAMP FOREST - Maman Turjaman; Hideyuki Saito; Erdy Santoso; Agung Susanto; Sampang Gaman; Suwido Hester Limin; Masato Shibuya; Kunihide Takhashi; Yutaka Tamai; Mitsuru Osaki; Keitaro Tawaraya (Jurnal Penelitian Ekosistem Dipterokarpa, 2007)
Trees of the Dipterocarpaceae dominate the tree vegetation in the tropical forests in Southeast Asian and they play important roles ecologically and econimcally. However, dipterocarps species have been reduced in number due to overexploitation. Seedlings of Shorea balangeran (Korth.) Burck were inoculated with spores of four ectomycorrhizal (ECM) fungi, Calvatia sp., Boletus sp., Scleroderma sp. and Strobilomyces sp., and were grown in pots containing sterilized peat soil for six months under nursery conditions and transplanted in field conditions. Four ECM fungi were collected from peat soil of Nyaru Menteng, Palangka Raya, Central Kalimantan. Six-months-old inoculated seedlings were transplanted into degraded peat-swamp forest. The ECM fungal colonization was 59-67% in inoculated seedlings under nursery conditions. Colonization of S. balangeran (Korth.) Burck increased shoot height, stem diameter, leaf number, and shoot fresh and dry weight 6 months after transplanting under nursery conditions. Shoot height, stem diameter, leaf number and survival rates of S. balangeran (Korth.) Burck were higher in the inoculated seedlings 40 months after transplanting under field conditions than in the control seedlings. It is suggested that inoculation of indigenous ECM fungi in native tree species is useful for reforestation of degraded peat-swamp forests.